Winners of the 2024 Tu Youyou Award - RuAngelie Edrada-Ebel; Angelo Fontana; Hideaki Kakeya; A. Douglas Kinghorn; Wei Li; Diana C. G. A. Pinto; Thomas E. Prisinzano; Binghe Wang (Molecules)
Professor Tu Youyou is a renowned Chinese scientist whose pioneering work led to the discovery in the 1970s of the antimalarial sesquiterpene lactone, artemisinin (qinghaosu), from the sweet wormwood tree, Artemisia annua L [...]